Parity as radical pragmatism: Centering farm justice and agrarian expertise in agricultural policy - Graddy-Lovelace, Garrett; Krikorian, Jacqueline; Jewett, Andrea; Vivekanandan, Avinash; Stahl, Katherine; Singh, Indra Shekhar; Wilson, Brad; Naylor, Patti; Naylor, George; Pennick, Edward Jerry (Frontiers in Sustainable Food Systems, 2023)
Rather than treating symptoms of a destructive agri-food system, agricultural policy, research, and advocacy need both to address the root causes of dysfunction and to learn from longstanding interventions to counter it. Specifically, this paper focuses on agricultural parity policies – farmer-led, government-enacted programs to secure a price floor and manage supply to prevent the economic and ecological devastation of unfettered corporate agro-capitalism. Though these programs remain off the radar in dominant policy, scholarship, and civil society activism, but in the past few years, vast swaths of humanity have mobilized in India to call for agri-food systems transformation through farmgate pricing and market protections. This paper asks what constitutes true farm justice and how it could be updated and expanded as an avenue for radically reimagining agriculture and thus food systems at large. Parity refers to both a pricing ratio to ensure livelihood, but also a broader farm justice movement built on principles of fair farmgate prices and cooperatively coordinated supply management. The programs and principles are now mostly considered “radical,” deemed inefficient, irrelevant, obsolete, and grievous government overeach—but from the vantage, we argue, of a system that profits from commodity crop overproduction and agroindustry consolidation. However, by examining parity through a producer-centric lens cognizant of farmers‘ ability, desire, and need to care for the land, ideas of price protection and supply coordination become foundational, so that farmers can make a dignified livelihood stewarding land and water while producing nourishing food. This paradox—that an agricultural governance principle can seem both radical and common sense, far-fetched and pragmatic—deserves attention and analysis. As overall numbers of farmers decline in Global North contexts, their voices dwindle from these conversations, leaving space for worldviews favoring de-agrarianization altogether. In Global South contexts maintaining robust farming populations, such policies for deliberate de-agrarianization bely an aggression toward rural and peasant ways of life and land tenure. Alongside the history of parity programs, principles, and movements in U.S., the paper will examine a vast version of a parity program in India – the Minimum Support Price (MSP) system, which Indian farmers defended and now struggle to expand into a legal right. From East India to the plains of the United States and beyond, parity principles and programs have the potential to offer a pragmatic direction for countering global agro-industrial corporate capture, along with its de-agrarianization, and environmental destruction. The paper explores what and why of parity programs and movements, even as it addresses the complexity of how international parity agreements would unfold. It ends with the need for global supply coordination grounded in food sovereignty and solidarity, and thus the methodological urgency of centering farm justice and agrarian expertise.